The Implementation of the Scandinavian Model of Welfare State in the Swedish Economic Development - Arum Tri Utami (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
This journal discusses how the welfare of the Scandinavian state became one of the main factors of Sweden's economic progress. The author uses qualitative methods to analyze how Sweden implements a welfare state as Sweden's main economic policy. The welfare state itself is a system where the government takes a strong role in reducing existing inequalities through various social programs. Sweden implements a comprehensive welfare state by collecting high taxes on the community and then channeling them back to the community with various social programs. Various programs that continue to be maintained by the government are health insurance for Swedish citizens, assistance to people who do not have jobs, health assistance for children, and pension assistance